Joint action in an elite rowing pair crew after intensive team training: The reinforcement of extra-personal processes - R'Kiouak, M.; Saury, J.; Durand, M.; Bourbousson, J. (Human Movement Science, 2018)
The present study is a follow-up case report of the study from R`Kiouak and colleagues (2016). From the initial study that analyzed how individual experts rowed together while they never had practiced together, we seized here the opportunity to investigate how both rowers synchronize after having intensively practiced joint action through a national training program in which they were invited to take part. The joint action of 2 individual expert rowers, which composed a coxless pair crew, was tracked on-the-water at the end of a team-training program. We first determined how each rower experienced the joint action at each instance of oars` strokes during a 12 min race. A phenomenological analysis evidenced several categories of how rowers shared lived experiences of their joint action. From mechanical data captured through an automatic recording device, we then scrutinized the mechanical signatures that correlated with each phenomenological sample. By comparing the present case report to the initial study, results suggested that, after the training program (a) rowers shared more meaningful experience of their joint action, and (b) only the boat velocity`s index contributed to explain why oars stroke were alternatively lived as effective or detrimental. The present case report thus suggests that joint action training in rowing might imply an increase in the joint sense-making activities, probably associated with a change from an inter-personal to an extra-personal meaningful mode of coregulation of the joint action. AUTORREFERAT